Importance of intestinal health in broilers (Research, Society and Development, 2020)
The intestinal health makes it possible to maintain the efficient and sustainable physiology of the gastrointestinal tract of birds. The gastrointestinal tract has digestive, absorptive, metabolic, immunological and endocrine functions. Thus, impaired intestinal health can systematically affect various functions of the body. The objective of this review is to characterize the importance of intestinal health in broilers. The methodology adopted was the bibliographic study, and the information obtained from documentary sources. Gastrointestinal functionality was found to be the stable state in which the microbiome and intestinal tract exist in symbiotic balance, with animal welfare and performance not restricted by intestinal dysfunction. Gastrointestinal functionality has gained prominence in poultry because of the growing demands for economic efficiency, welfare, food security, reduction of environmental impacts and restrictions on the use of performance enhancing antimicrobials. Among the essential factors for bird intestinal health are the care of chicks in the first weeks of life, enteric diseases, the quality of feed ingredients and the use of additives that favor the preservation of enterocytes. The intestinal health of broiler chickens is an important characteristic to be maintained and observed in poultry production. A healthy gut is necessary so that the bird can properly perform the physiological processes inherent in its organism and express its productive potential, with diet manipulation being a promising strategy for positively modulating the intestinal microbiota of poultry. The use of agents that have trophic effects on intestinal mucosa contributes to improve the digestibility of nutrients, growth performance and intestinal health of broilers.